The constructive methods of teaching mathematics - Jasutienė, Eglė (Lietuvos matematikos rinkinys, 2021)
The problem of teaching mathematics in Lithuanian schools envisaged in this article. The teachers often use the teaching methods of behaviourism. The widely used teachingmethods of constructivionism in the world are appearing in Lithuanian schools too. There is talked how mathematics teachers can easier start to use new progressivemethods by using IT in this article. There is reviewing how start to use constructive mathematics teaching methods by using Geometer’s Sketchpad in this article. There was appeared some problems for teachers by using Geometer’s Sketchpad in schools. So these problems help to find new step of investigating Geometer’s Sketchpad in teaching mathematics – to built the various sets of dynamic sketches for teaching and learning mathematics in basic schools. More than 800 dynamic sketches have been developed within 9th and 10th grades mathematics curriculum. Now is preparing set of sketches for 11th and 12th grades. Some constructive methods of teaching mathematic by using these sets of sketches are discussed in this article. The methods of comparative analyze and of synthesis of scientificworks are used in this article.